EVALUASI PERKEMBANGAN TERNAK SAPI GADUHAN MELALUI DINAS PERTANIAN DAN PERIKANAN DI DISTRIK ARSO BARAT - Suparman; Kondong, Dortje Janet (STIPER Santo Thomas Aquinas Jayapura, 2022)
The purpose of this study was to determine the development of Gaduhan Cattle (Sapi Gaduhan) by theGovernment to farmers in the West Arso District that has been executed according to the applicableprovisions in a cooperation agreement and provides benefits for both parties.The research method usedsurvey methods, interviews, documentation. Research variables consist of 3 variables, that are: 1.Procedure for determining candidate farmers/candidate locations (CP/CL); 2. Work Agreement with theGovernment; 3. Development of Gaduhan Cattle. The development of Gaduhan cattle in West ArsoDistrict from the initial number of 104 heads which details the final stock of 381 heads. This developmentis influenced by the management and supervision by the Department of Agriculture and Fisheries,assistance and guidance to farmers/groups